Alternative migratory strategies are widespread in subyearling Chinook salmon. Issue 1 (23rd August 2020) - Apgar, Travis M.; Merz, Joseph E.; Martin, Benjamin T.; Palkovacs, Eric P.
Abstract: Variation in life history traits within and across species is known to reflect adaptations to different environmental drivers through a diversity of mechanisms. Trait variation can also help buffer species and populations against extinction in fluctuating environments and against anthropogenic disturbances. Here, we examine the distribution and drivers of Ocean‐type Chinook salmon ( Oncorhynchus tschawytscha ) juvenile migratory life histories. We defined alternative migratory strategies according to whether individuals reared in the stream ( natal rearing ) or left shortly after hatching to rear elsewhere ( non‐natal rearing ). We then evaluated the frequency of migratory strategies across 16 populations with time series extending up to 25 years and evaluated the environmental variables that influenced variation in migration strategy. We found bimodal migration patterns and abrupt transitions in migrant sizes across all populations, supporting the widespread nature of alternative migratory strategies. Additionally, we found that the amount of freshwater rearing habitat available to juveniles, relative juvenile density and spring flow patterns significantly influenced the overall migration pattern for populations. Smaller streams and higher conspecific densities generally produced more non‐natal rearing migrants and larger streams and lower conspecific densities producing more natal rearing migrants. Our results shed light on previously unexplored patterns of juvenile migratory strategies and encourage broader consideration for how current conservation actions perform at protecting juvenile migratory diversity.